Design of multirecess hydrostatic oil journal bearings - Ghosh M.K.; Majumdar B.C. (My University, 2025)
This paper presents computer generated design data in terms of load capacity and oil flow for multirecess hydrostatic journal bearings. The Reynolds equation for a finite bearing was solved on a high speed digital computer satisfying appropriate boundary conditions and using the finite difference method. Results for various L/D ratios, recess to bearing area ratios, number of recesses etc are presented for capillary and orifice compensated bearings. © 1980.